Migratory insertion in N-heterocyclic carbene complexes of palladium; an experimental and DFT study - Danopoulos, Andreas A.; Tsoureas, Nikolaos; Green, Jennifer C.; Hursthouse, Michael B. (Chemical Communications, 2003)
The first authenticated example of migration of a methyl group from palladium(ii) to a coordinated N-heterocyclic carbene is described. © 2003 The Royal Society of Chemistry.